PENINGKATAN NUTRISI LIMBAH PRODUKSI BIOETANOL DARI SINGKONG MELALUI FERMENTASI OLEH KONSORSIUM Saccharomyces cereviseae dan Trichoderma viride - Rahmat Taufiq Mustahiq Akbar; Yani Suryani; Iman Hernaman (JURNAL ISTEK, 2014)
Bioethanol is a renewable bio-fuels as an alternative energy substitute for oil, in the process leaving a solid waste that can be leveraged into a more useful product. This study aims to improve nutrition and reduce HCN and get the right dose of inoculum in the fermentation of bioethanol from cassava waste. This research was conducted with the experimental method used Completely Randomized Design (CRD) in the 3 x 3 factorial with 3 replications. The first factor inoculum dose (D) to the level of inoculum dose, respectively d1 = 2%, 3% = d2, d3 = 4% and the second factor is the length of fermentation, namely for 0, 4 and 8 days As for some of the parameters measured were protein content and crude fiber through proximate analysis, as well as levels of HCN by distillation method. The result showed that the best dose is the dose of 4% which can increase protein content from 2.47% to 2.91% before fermentation - 4.88% after fermentation and can lower crude fiber content of 2.65% to 2.50 % - 2.07% and influential to the decreased levels of HCN from 15.92 mg / kg to 12.73 mg / kg - 0.00 mg / kg for 8 days after fermentation. The results showed that the fermentation process using a consortium of Saccharomyces cerevisiae and Trichoderma viride can improve the quality of solid waste processing bioethanol from cassava which include increased levels of protein, crude fiber and decreased levels of HCN reduction.